Significado dos alimentos locais na perspectiva dos profissionais de gastronomia de Mato Grosso do Sul - Alexandro Moura Araujo (2021)
The state of Mato Grosso do Sul stands out for food production, coexisting both systems with greater technological input, focused on commodities, and more traditional ones, which supply the national and local market. Thus, the objective of this study is to analyze the use of local foods by gastronomy professionals in MS. Thus, it seeks to understand the variables surrounding the judgment and meaning of these foods, as well as the factors affecting the intention to purchase these products by these professionals. Using a mixed exploratory sequential approach, we collected primary data through interviews and self-administered questionnaires with gastronomy professionals in MS. The results indicated that vegetables are the main products purchased from local producers, in addition to some processed products. The use of a local food is due to the feeling of responsibility towards the producers (in order to value them), in addition to the freshness and taste attributes. From the application of the Two Route Model (MDR), proposed by Allen (2000), it was found that participants tend to make a more fragmented (step-by-step) judgment in choosing local foods, and the meaning of the food is related to the utility that the products have. The research also revealed some obstacles to the acquisition of these products, such as the unavailability of some items at certain times of the year, the lack of compliance with the sanitary regulations in force, and the informality of the producer. Despite this, it was found that there is an effort by gastronomy professionals to use local ingredients in their menus.